2011
DOI: 10.1177/8756087911410592
|View full text |Cite
|
Sign up to set email alerts
|

Physical characterizations of three phase polycarbonate nanocomposites

Abstract: Zinc oxide-Barium titanate-Polycarbonate (ZnOÀBaTiO 3 ÀPC) nanocomposites were prepared to investigate effect of ZnO-BaTiO 3 mixed nanoparticles on the optical, electrical, and thermal properties of polycarbonate (PC). The UV-visible absorption spectra was measured for the nanocomposites at room temperature between 200 and 800 nm and the optical energy gap was determined from the measured absorption coefficient data. Optical results reveal that BaTiO 3 ceramic has a strong absorption below 300 nm while ZnO has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In the continuity of our ongoing studies 1,15 19 into the MWCNTs with different neat polymers such as polystyrene, polycarbonate, and so on, in the present study, a novel dispersion behavior of MWCNTs was obtained through pretreatment of MWCNTs at different pH values. In our previous work, 1 we functionalized MWCNTs with β-HNA and observed that β-HNA molecules adsorb onto the surface of MWCNTs due to inherent hydrophobic/hydrophilic sites and create electrostatic charge on the surface.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…In the continuity of our ongoing studies 1,15 19 into the MWCNTs with different neat polymers such as polystyrene, polycarbonate, and so on, in the present study, a novel dispersion behavior of MWCNTs was obtained through pretreatment of MWCNTs at different pH values. In our previous work, 1 we functionalized MWCNTs with β-HNA and observed that β-HNA molecules adsorb onto the surface of MWCNTs due to inherent hydrophobic/hydrophilic sites and create electrostatic charge on the surface.…”
Section: Introductionmentioning
confidence: 79%
“…Besides, commercial thermoplastic polymer such as polyethylene (PE), polypropylene (PP), poly (vinyl alcohol) ( PVA), polyvinyl chloride (PVC) ….etc are the mostly and widely used plastic in the industrial applications because they are cheap, durable, hard, and easily worked. 1 20 Despite of the extensive studies 1 27 of such materials, multiwalled carbon nanotubes (MWCNTs)-polymer nanocomposites, many important aspects of the electronic and optical properties of these materials are still not fully resolved. Consequently, it will be very interesting to study the effect of pretreatment of MWCNTs using a new method to improve their dispersion in neat polymer to obtain polymer nanocomposites that have attractive properties for industrial applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many research groups increased the energy density of dielectric capacitors using a nanocomposite approach, including barium titanate (BaTiO 3 ) nano particles reinforced polycarbonate (PC) [10], poly(vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) [11], modified BaTiO 3 nanoparticle with PVDF [12,13], titanium dioxide (TiO 2 ) nanoparticles with PVDF terpolymer [14], calcium copper titanate (CCT) reinforced polyimide [15], silver nanoparticle/poly (vinyl pyrrolidone) core-shell structure for high dielectric constant and low loss epoxy matrix composite [16], and PZT or PLZT powders reinforced PVDF [1,17].…”
Section: Isrn Nanomaterialsmentioning
confidence: 99%
“…Polycarbonate (PC) is an important thermoplastic engineering polymer having fine processing, thermal, mechanical, and optical properties. 1,2 PC blends are well-known commercial products due to complementary component properties. PC materials have received considerable attention in academia and technical applications particularly in construction, automotive, aerospace, and electronic industries.…”
Section: Introductionmentioning
confidence: 99%